Designing and Evaluating Jotform-Based Instrument for Assessing Students' Multiple Representational Skills - Erwin Saputro; Elvin Yusliana Ekawati; Fairusy Fitria Haryan (Unnes Science Education Journal, 2026)
Phenomena in physics are often presented in various forms, such as equations, verbal, graphs, tables, and images, which require multiple representation skills in understanding and describing natural phenomena correctly. Effective development of students’ multiple representational skills requires prior assessment of their existing representational abilities. This study aims to develop a JotForm-assisted multiple representation ability assessment instrument for Phase F students on linear Motion material and to examine its design qualitatively. The research uses the 4D model, to produce a prototype that is ready to be tested. Data were obtained through documentation and interviews, including literature review, curriculum analysis, and needs identification. At the design stage, it begins with selecting the question material to be used, preparing a multiple representation assessment instrument, creating a design with JotForm, and compiling guidelines. A qualitative review of the instrument design was conducted by two experts in physics learning and physics learning evaluation and 4 practitioners from SMA 4 Surakarta and SMA 3 Boyolali. The review results showed that the assessment design, which consisted of 15 questions, was suitable for further development.